2016
DOI: 10.1016/j.ecolind.2015.01.042
|View full text |Cite
|
Sign up to set email alerts
|

A remote sensing spatio-temporal framework for interpreting sparse indicators in highly variable arid landscapes

Abstract: a b s t r a c tThe world's extensive and often remote arid landscapes are receiving increasing attention to maintain their ecological and productive values. Monitoring and management of these lands requires indicators and evidence of ecosystem condition and trend, generally derived from widely distributed and infrequently repeated site-based records. However adequate geographic representation and frequent site revisits are difficult to achieve because of the remoteness and vast extent of these landscapes. Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Natural ecosystem and ecoenvironmental vulnerability are sensitive to changes in land use/land cover (LULC) (Boori and Amaro, 2011;Xie et al, 2013;Hao and Ren, 2009;Adger, 2006;Valipour, 2015Valipour, , 2016. Decision makers are increasingly pressured with challenges of pursuing social and economic developments without causing detrimental impact on the environment (Hinkel, 2011;Ostendorf, 2011;Lawley et al, 2016). While there might have strong correlations among eco-environmental health, LULC, and thermal signatures (Strand et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Natural ecosystem and ecoenvironmental vulnerability are sensitive to changes in land use/land cover (LULC) (Boori and Amaro, 2011;Xie et al, 2013;Hao and Ren, 2009;Adger, 2006;Valipour, 2015Valipour, , 2016. Decision makers are increasingly pressured with challenges of pursuing social and economic developments without causing detrimental impact on the environment (Hinkel, 2011;Ostendorf, 2011;Lawley et al, 2016). While there might have strong correlations among eco-environmental health, LULC, and thermal signatures (Strand et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…() used Landsat time series data, similar to that used here, to predict vegetation structure using magnitude and duration of the greatest disturbance, the time since disturbance and current index value, and a similar approach was used to understand vegetation patterns in arid areas (Lawley et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Computationally, regionalisation also reduces the data to be processed, as well as the spectral variability and analytical complexity per dataset. Regionalisation should be created at characteristic spatial-temporal scales that recognise both landscape variation and key ecological processes over time [45]. Venkatappa et al [46] identified phenological periods from time series curves that displayed optimal separations in vegetation index values of land cover classes.…”
Section: Consequences Of Different Forest Definitions and Issues With...mentioning
confidence: 99%